The LITTability study - evaluation of the applicability of LITT in a real-world cohort of glioma patients - Kaes, Manuel; Rondinelli, Vincenzo; Krieg, Sandro; Jakobs, Martin (Neurosurgical review, 2025)
Laser-interstitial thermal therapy (LITT) is a minimally invasive technique used in neurosurgery for ablation of epileptic foci and malignant lesions, especially for glioma located in regions that pose high surgical risk. Current research mainly focuses on maximizing the safety of the procedure and proving the non-inferiority compared to open resection of glioma. However, data regarding the current applicability in real-time cohorts are lacking. The goal of this study is to evaluate the real-world applicability of LITT in glioma patients, specifically focusing on those who had undergone stereotactic biopsy, and to define limiting factors. For this retrospective study, we analyzed n = 207 glioma patients from a monocentric stereotactic surgery database over a 5-year period (2018-2022). Clinical, histopathological and radiological data were assessed. To define a lesion suitable for LITT, a two-step approach was used. In a first step, predefined selection criteria were applied consisting of a Karnofsky Performance Score of 70 or higher, an ASA Score of 3 or less, MRI compatibility, and glioma presenting as a single or bifocal lesion. In a second step, the LITT simulation was performed with additional criteria consisting of at least 90% possible ablation volume, a safe trajectory with avoidance of vessels, and optimal lesion accessibility without brainstem involvement. Out of 207 patients, 137 cases met initial preselection criteria, while 36 cases (17.4%) were ultimately deemed suitable for LITT post-simulation. Common exclusion factors included multifocal lesions, irregular lesion shape, and size constraints. Among suitable cases, 94.4% had unifocal lesions. For 44.4% of cases, only a single catheter was needed, with the number of ablation points varying from one to twelve per trajectory. The average lesion diameter for LITT-suitable cases was 26.4 mm. Even though LITT offers a promising alternative for glioma not suitable for open resection, the current application is limited. Main reasons were due to lesion morphology and size. Enhancing LITT applicability could involve addressing constraints posed by lesion geometry and volume. Prospective studies comparing LITT with conventional resection could better define the subset of glioma patients who may benefit most, advancing the potential for LITT in clinical neurosurgical practice.
Online veröffentlicht: 03. Juni 2025
Gesehen am 11.09.2025